Just How Deterring Are Formulas? - Strahl, Alexander; Müller, Rainer; Hagendorf, Susan; Grobe, Julian (Scientia in educatione, 2017)
Formulas are an effective means for communication in physics. Most teachers would agree, however, that novices tend to be deterred by formulas. Up to now, this common belief has never been substantiated by quantitative research. Here we report on an attempt to identify and quantify the variables that govern the appraisal of physical formulas. In an empirical study, 684 secondary school and university students were asked to indicate for 38 formulas to which extent they perceive the formula as deterring. The result is surprisingly simple. We are able to model the responses with only a single variable: the length of the formula. An explicit model equation (saturating exponential) to fit the data can be given.